Maternal periodontitis and adverse pregnancy outcomes - Pitiphat W, Joshipura KJ, Gillman MW, Williams PL, Douglass CW and Rich- (Blackwell Synergy, 2008)
Maternal periodontal diseases have been associated with increased risk of preterm birth and restricted fetal growth among relatively low socioeconomic groups.